Theology for ministry - Lavin, Margaret (Quezon City : Claretian Publications, 2007)
"More and more people today are involved in ministry in some way: as lay pastoral assistants, chaplains, pastors, youth group leaders and more. But what is ministry? How do we do ministry, and why? In theology for Ministry, Margaret Lavin leaders readers through underlying theological themes of this form of service- who we believe our God is, and who we are in relationship to God-in order to show how they inform what we do in ministry. Lavin's faith-filled approach draws out the pastoral implications of these themes and reminds us that each of us is called to minister in some way to larger community. In her own words, " Our mandate to minister is deeply embedded in the Christian understanding of the human condition." This resource will help those involved in ministry to find the theological roots they need in order to support and enrich their work with those around them as they grow in faith together.
Ecclesiology: the church as trinitarian community
Includes bibliographical references.
Keywords: Pastoral theology -- Catholic Church